Conceptualización, registros de representaciones semióticas y noética: interacciones constructivistas en el aprendizaje de los conceptos matemáticos e hipótesis sobre algunos factores que inhiben la devolución - D’Amore, Bruno (Revista Científica, 2011)
This study derives inspiration from the original discusions of Raymond Duval (1988a, b, c; 1993), and forms part of the research being done by the nrd of Bologna University. It atempts to draw out and to substabtiate the diferentes hypotheses that lie at the foundations of unsuccesfull devolution (Perrin G., 1994), and therefore also at the foundations of the schoolong of mathematical awarenes (D’Amore, 1999a).